The evaluations range of Czechoslovak legionaries in Russian literature - Nina Vladimirovna Barkovskaja (Opera slavica, 2018)
Based on the material of memoirs and literary works of different years, the changes in the assessments of the activity of Czechoslovak legionaries in the Urals are considered. The dependence of the assessment criteria on the prevailing ideological orientation in a particular period of the history of Russia in the twentieth century is shown. The conclusion about the contradictory image of Czechoslovak legionaries in the modern "memory of the place" is made. The idea of the "third way" in actual interpretations of the events of the Civil War in the Urals is accentuated, and an attempt to show the development of the events of the twentieth century in the "if not…" aspect in Vladimir Karzhavin's novel about General Wojciechowski also being made.